Formulating a Policy for Developing Regional Solid Waste Final Disposal Installation in East Java Province - Hitapriya Suprayitno; Bieby Voijant Tangahu (Jurnal Manajemen Aset Infrastruktur & Fasilitas, 2018)
Solid Waste Final Disposal Installation is capital for urban area. Meanwhile, cities, in general, do not have enough space to build Final Disposal Installation. They need to collaborate with the neighboring district. Such collaboration does not always run well. Therefore, provincial government needs to participate in it by developing Regional Final Disposal Installation to be used together. A policy, for developing this, need to be formulated. A special method, Step by Step Highest Solution Reduction by Needs and Constraints, has been used to formulate the policy. The main policy formulation for developing Regional Solid Waste Final Disposal Installation consists of several following lines : to develop Regional Final Disposal Installation for all cities step by step in function of the city needs; to develop incineration type final disposal step by step in function on the financial disponibility; to push the rich cities to develop solid waste incineration step by step; to push implementation of 3R techniques starting from intermediate disposal installation step by step; to forbid the utilization of open truck for transporting domestic solid waste from intermediate disposal to final disposal step by step; to maintain the existing city sanitary landfill final disposal and transforming it into incineration installation step by step; to promote facilitiies installation made by Indonesian industry, to develop a good institutional arrangement for the Regional Final Disposal Installation.